Moringa oleifera Lam. Peptide Remodels Intestinal Mucosal Barrier by Inhibiting JAK-STAT Activation and Modulating Gut Microbiota in Colitis - Hong, Zi-Shan; Xie, Jing; Wang, Xue-Feng; Dai, Jing-Jing; Mao, Jia-Ying; Bai, Yu-Ying; Sheng, Jun; Tian, Yang (Frontiers in Immunology, 2022)
Ulcerative colitis is a chronic inflammatory bowel disease (IBD), but progress in exploring its pathogenesis and finding effective drugs for its prevention and treatment has stalled in recent years. The seeds of Moringa oleifera Lam. are rich in proteins known to have multiple physiological activities. In our earlier work, we had isolated and purified a peptide (MOP) having the sequence KETTTIVR, from M. oleifera seeds; however, its anti-inflammatory activity and mechanism in vivo were unclear. Here we used the dextran sulfate sodium (DSS)-induced colitis model to study the anti-inflammatory activity and mechanism of this MOP. Our results are the first to show that MOP can ameliorate the pathological phenotype, inflammation, and intestinal barrier disruption in mice with colitis. Furthermore, RNA sequencing revealed that MOP inhibits the Janus kinase/signal transducer and activator of transcription (JAK-STAT) pathway activation. Next, by using 16s rRNA gene sequencing, we found that MOP can ameliorate DSS-induced gut microbiota dysbiosis. In addition, an untargeted metabolomics analysis suggested that MOP is able to modulate the level of lipid and amino acid metabolites in IBD-stricken mice. Altogether, these results indicate that MOP ameliorates colitis by remodeling intestinal mucosal barrier by inhibiting JAK-STAT pathway’s activation and regulating gut microbiota and its metabolites, thus providing a basis for further processing and design of bioactive foods from M. oleifera seeds.